"Showing Up America": Performing Race and Nation in Britain Before the First World War. (25th October 2022) - Defrates, Lewis
Abstract: This article examines American travel and performance in Britain in the decades prior to the First World War, arguing that the expression of nationality in this transatlantic context played a profound role in formulating both America's dominant culture and a culture of opposition advanced by African American performers. It explores this "oppositional" culture in detail, focusing on the transatlantic work of Ida B. Wells and the Fisk Jubilee Singers. Both found a sympathetic audience across the Atlantic at a time of increased repression at home. British support opened new avenues for these activists, but also limited the rhetorical possibilities of their work. By bringing into conversation previously separate historiographies on early waves of "Americanization, " the transnational dimensions of various reform movements and the international formation of the Black Atlantic, it illustrates the economic, infrastructural, and racial inequalities that shaped the United States' emerging national culture.